PEMANFAATAN GOOGLE FORM DALAM OPTIMALISASI PENDATAAN SKPD DI KABUPATEN SIKKA: STUDI DESKRIPTIF KUALITATIF PADA DINAS KOMINFO MAUMERE - Sergiana Dai Padak; Mayelus Dori Bastian; Viktor Ariestyan Sedu (LPPM Universitas Abdurrab, 2025)
Optimizing data collection from Regional Work Units (SKPD) is one of the challenges for the Sikka Regency Communication and Information Service (Kominfo) in supporting the efficiency of government administration. This research aims to analyze the use of Google Form as a tool in the SKPD data collection process. The research method used is descriptive qualitative, with data collection techniques via Google Form distribution links to various relevant Regional Apparatus Organizations (OPD) in Sikka Regency. The research results show that using Google Forms provides several significant benefits, such as ease of access, reduced data processing time, and increased information accuracy. Apart from that, this implementation also saves operational costs compared to manual methods. However, some of the challenges faced include low technological literacy in some OPDs and dependence on internet access. This research concludes that Google Form is an effective and efficient solution to support the digitization of SKPD data management. The recommendations provided include technology training for OPD staff and strengthening digital infrastructure to support optimal use of technology in government.